(untitled) (Nordic Journal of African Studies, 2004)
Cameroon’s democratic train appears to be moving in the opposite direction following a brief spell of euphoria that heralded the re-introduction of political pluralism in 1990. What was believed by many observers to be a revolution that was going to usher in a system of governance on the foundation of Social Justice is petering out. Rather, the country is mired in generalized poverty, social discord, and a return to the political high-handedness characteristic of the post-independence monolithic political period. Several reasons, including efforts by anti-democratic forces to regain the political and economic privileges associated with autocratic rule, have been adduced for this policy roll-back. This paper uses a historical and analytic framework to discuss some reasons for this democratic hold-up in Cameroon’s political and social transition within the broad and ongoing democratization process in Sub-Saharan Africa.